Masalah dan Kendala Dukungan APBN dalam Sektor Pertanian: Telaah Literatur - Dahiri Dahiri (Pusat Kajian Anggaran, 2021)
The agricultural sector is one sector that plays an important role in the domestic economy. However, there are still obstacles in the implementation of budget support for the agricultural sector. The purpose of this study is to analyze the budget support for the agricultural sector. While the data used in this study is secondary data obtained from the website of the Ministry of Agriculture and the State Budget Financial Note, as well as agencies related to the agricultural sector. The data analysis method used is descriptive statistics that describe the data from the information obtained. The results showed that there were several problems, for example, the fertilizer distribution system, regulations, and technicalities of DAK Irrigation, socialization and administration of Agricultural DAK, decreased planting area and productivity, rice imports, dependence on imports of fresh horticultural products, decreased planting area for leading plantation commodities, and distribution of agriculture machinery which focus only on pre-harvest and not right on target, decreased seed production capacity of superior varieties, low level of education of farmers and the limited number and quality of agricultural extension officers in the field, and not yet the optimal realization of Food Security Agency activities, especially in the regions.